Enhancing physical activity coaching through personalized motivational strategies and self-adaptive goal-setting: development of self-adaptive processes in a monitoring and coaching smartphone application - Cabrita, Ana Miriam Meireles Ferreira (2013)
Dissertação para obtenção do Grau de Mestre em Engenharia Biomédica